Path Tracing Bidirecional em GPU: implementação e análise - Régis, Christopher Philippe Diniz (2019)
Nowadays more and more people are looking for realistic visual experiences through games, videos or movies, where all these products basically consist of generation and display of images. One of the ways to generate realistic images is to faithfully reproduce the lighting effects that occur in the real world, such as shadows, reflections, refractions, among others. One of the main techniques used to generate realistic images is the path tracing algorithm. However, the technique has limitations when rendering images of scenes where most of the geometry is not directly illuminated by light sources. In this context, the bidirectional path tracing algorithm appears, which functions as an extension of the original algorithm and seeks to obtain better results. This work consists of the implementation of the bidirectional algorithm and subsequent comparison with other variations of the algorithm. The results obtained confirm that the bidirectional algorithm is more efficient when rendering images where most of the geometry is not directly illuminated. However, the algorithm presents a higher computational cost, which can make its use unfeasible in some situations.